Carbide in-situ reinforced high-temperature high-strength wear-resistant material as well as preparation method and application thereof
By combining Ni and M2AlC phases and using powder metallurgy to prepare carbide-in-situ enhanced high-strength anti-wear materials, the problem of insufficient mechanical properties and wear resistance at high temperatures is solved, and the optimization and unity of the mechanical properties and friction wear properties of the material at high temperatures is achieved.
Patent Information
- Application Number
- CN202411701717.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
Existing high-temperature and wide-temperature domain materials have shortcomings in mechanical properties and tribological properties, especially the problems of low mechanical properties and wear resistance at high temperatures.
Carbide-in-situ enhanced high-temperature and high-strength anti-wear materials were prepared by compounding Ni and M2AlC phases and using powder metallurgy method (ball milling + vacuum hot press sintering). During the hot press sintering process, Ni-based solid solution, Ni3Al, NiAl and other matrix phases and VCx and NbCx carbide reinforced phases are generated in situ to form a material with high strength and wear resistance.
It achieves the optimization and unity of the mechanical properties and friction wear properties of the materials at high temperatures, and has good tensile, compressive strength and low wear rate. It is suitable for aero engine parts, high-performance cutting tools and drilling tools, etc.
Smart Images

Figure CN119506660A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material design and preparation, and in particular to a carbide in-situ enhanced high-temperature and high-strength wear-resistant material and a preparation method and application thereof. Background Art
[0002] With the rapid development of high-tech industries such as aviation, aerospace, nuclear engineering, and energy and power, higher and higher requirements are placed on the performance of materials serving under extremely harsh working conditions (such as high temperature, high speed, ultra-high load, special media and atmosphere). For example, the mating surface between the turbine blades and the outer ring, the blade crown, high-performance cutting, and drilling tools of aircraft engines have put forward more urgent demands for materials with high strength and low wear at high temperatures (~1000℃). At the same time, due to the improvement of the thrust-to-weight ratio of aircraft engines, etc., lightweight materials have become a trend.
[0003] There are patent reports on materials with good tribological properties in high temperature and wide temperature range (self-lubricating composite materials). Chinese patent CN109402435A discloses a nickel-aluminum-based wide temperature range self-lubricating alloy and its preparation method, which has a friction coefficient of 0.20-0.50 in the range of room temperature to 1000°C and a wear rate of 1.2*10 -5 ~24*10 -5 mm 3 / Nm. Chinese patent CN103572137A discloses a NiCr-Al2O3 self-lubricating composite material and its preparation method, the friction coefficient of which is 0.274-0.475 at room temperature to 1000℃, and the wear rate is 0.546*10 -5 ~8.31*10 -5 mm 3 / Nm. Chinese patent CN109666815A discloses a preparation method and application of a MAX phase reinforced nickel-based high-temperature lubricating composite material, which mainly focuses on the preparation of MAX phase Ti3SiC2 material. After Ti3SiC2 powder is prepared, it is mixed with NiAl powder to prepare NiAl-Ti3SiC2 composite material. The friction coefficient (0.21-0.27) and wear rate (5.9*10 -5 ~9.5*10 -5 mm 3 / Nm) is low. However, none of the above patents involve the mechanical properties of the materials. Chinese patent CN105441707A discloses a nickel-based self-lubricating composite material of compound graphite and lead (Pb), which has good lubrication and wear resistance at room temperature to 500°C, and has a high room temperature compressive strength (>300MPa). Chinese patent CN1360075A discloses a nickel-based self-lubricating alloy containing Fe, Co, Nb, Se, and graphite, which exhibits low friction and wear resistance in the range of room temperature to 600°C, but its compressive strength is low, the room temperature compressive strength is only 6.80~9.86MPa, and the 600°C compressive strength is 4.34~6.65MPa. The nickel-based self-lubricating alloys disclosed in Chinese patents CN1073727A, CN1082620A, CN1101681A, etc., achieve good tribological properties at room temperature to 700°C, but their mechanical properties in a wide temperature range are poor. Chinese patent CN105986147A discloses a wide temperature range nickel-based self-lubricating composite material and its preparation method. The material has a low friction coefficient and a low wear rate in the range of room temperature to 700°C, but its wear rate is still relatively high at 700°C (10 -4 mm 3 / Nm order of magnitude), and its mechanical properties at high temperature were not investigated. Chinese patent CN111440968A discloses a nickel-based wide temperature range high-strength self-lubricating composite material and its preparation method. The tensile strength of the material at 800°C is 124.7-262.0MPa, and the compressive strength is 280.2-398.7MPa; the tensile strength at 1000°C is 30.0-62.0MPa, and the compressive strength is 73.8-141.7MPa; the friction coefficient at 800°C is 0.23-0.33, and the wear rate is (3.09-4.67)10 -5 mm 3 / Nm, this material focuses on the optimization and unification of mechanical properties and tribological properties in a wide temperature range (room temperature to 800℃), and its mechanical properties and wear resistance at high temperatures are relatively low. Hu et al. compounded Ni and MAX phase Ti2AlC and Ti3AlC2 to produce a series of TiC xAs the reinforcement phase, Ni3(Al,Ti) / NiAl and Ni3(Al,Ti) / Ni are composite materials of the matrix phase, respectively. This series of composite materials has high tensile, compressive and elastic properties from room temperature to 800°C (Materials Characterization 135 (2018) 295-302, Journal of Alloys and Compounds 774 (2019) 739-747), Metals and Materials International 27 (2021) 3003-3012, Materials Science & Engineering A 697 (2017) 48-54, Journal of Alloys and Compounds 747 (2018) 1043-1052, 765 (2018) 987-993, etc.), but their tribological properties were not investigated. Zhang et al. compounded Ni and Ti3AlC2 to generate TiC and Ni2TiAl in situ. The material has excellent room temperature wear resistance and the elastic modulus increases with temperature at 500-800°C (Materials Science & Engineering A 597 (2014) 70-74), but did not investigate its mechanical properties and tribological properties such as tension and compression at high temperature. Gao et al. investigated the tribological properties of Ni / Ti2AlC composites at room temperature and high temperature (800°C), and reported its hardness and elastic modulus at room temperature, but did not investigate its mechanical properties such as tension and compression at high temperature (Wear 488–489 (2022) 204165, Journal of Tribology, Vol. 42, No. 2, 2022, 242-253). Yuan et al. investigated the friction and wear properties of NiAl-Ti3AlC2 composites at 600°C, but did not involve its mechanical properties (Materials Research Express, 2020.7, 026539). In summary, it is rare to consider both the high-temperature mechanical properties and tribological properties of materials in the existing public literature reports. At present, only a few literatures have examined both the high-temperature mechanical properties and tribological properties of materials. Among them, Liu et al. reported the compression properties of NiCr-40wt.% Al2O3 materials at room temperature to 1000℃ (TribologyInternational 84(2015)1–8), but the Al2O3 content was as high as 40wt.%, the material machinability was poor, and the tensile properties of the material were not examined.Yang Sulan et al. reported the tensile, compressive and friction and wear properties of Ni-based composite materials with different Mo element contents in a wide temperature range (room temperature to 1000°C) (Journal of the Chinese Society of Nonferrous Metals, Vol. 27, No. 11, 2267-2275). However, the high-temperature mechanical properties of the material were poor, with a tensile strength of only 20 to 23 MPa and a compressive strength of only 30.1 to 51.0 MPa at 1000°C. In addition, the material had poor wear resistance, with a wear rate of 10. -3 ~10 -4 mm 3 / Nm order of magnitude. Zhao et al. investigated the tensile, compressive and friction and wear properties of NiMoAl composite materials with Ag and MoS2 in a wide temperature range (RT~800℃) (Metals2020,10,268). The mechanical properties of this material are poor at high temperatures (tensile strength at 800℃ <50MPa, and the maximum compressive strength is only 140MPa). Zhao Gaopan et al. added Ta and / or Ag to Ni, Cr, Mo, and Al powders to prepare composite materials, and investigated their tensile and compressive properties at room temperature to 1000℃ and friction and wear properties at room temperature to 800℃ (Journal of Tribology, Vol. 41, No. 3, 393-403). The results showed that the composite material with Ta added alone had the highest mechanical properties, with a tensile strength of 42MPa at 1000℃ and a compressive strength of about 92MPa. However, this material focuses on the optimization and unification of mechanical and tribological properties in a wide temperature range, and the wear rate is relatively high at room temperature, reaching 2×10 -4 mm 3 / (Nm). Shan et al. prepared NCW10A5S5Ag composite material by powder metallurgy by mixing Ni, Cr, W, α-Al2O3, SrCO3 and Ag, and investigated the mechanical properties (tensile, compression, bending) and friction and wear properties of the composite material at RT~800℃ (Tribology International 183(2023)108433). The mechanical properties of the material are relatively low, with a maximum tensile strength of about 207MPa and a maximum compressive strength of about 1051MPa, and its wear rate at room temperature is 10 -4 ~10 -3 mm 3 / (Nm) order of magnitude.
[0004] In addition, the existing high-temperature or wide-temperature range lubricating and anti-wear materials have many kinds of raw materials, including matrix phase (Ni, Ni20Cr), strengthening elements (Al, Cr, Mo, W, etc., at least 2 to 3 kinds), strengthening phase (Cr2O3, Al2O3, carbide, etc., at least 1 kind), lubricating phase (Ag, graphite, MoS2, CaF2 / BaF2, SrSO4, SrCO3, 1 to 2 kinds), at least 4 to 5 kinds of raw materials are required. Therefore, it is of great significance to provide a material with simple raw materials that can achieve optimized and unified mechanical properties and friction and wear properties at high temperatures. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a carbide in-situ reinforced high-temperature and high-strength wear-resistant material and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a carbide in-situ reinforced high-temperature and high-strength wear-resistant material, which is prepared from raw materials containing the following molar fractions:
[0008] M2AlC phase 10-30%, Ni balance;
[0009] The M2AlC phase includes one or more of V2AlC, Nb2AlC and Ta2AlC.
[0010] Preferably, the particle size of the M2AlC phase is ≤20 μm, and the particle size of Ni is ≤48 μm.
[0011] The present invention also provides a method for preparing the carbide in-situ enhanced high-temperature and high-strength wear-resistant material, comprising the following steps:
[0012] The M2AlC phase and Ni are mixed, ball milled and sintered in sequence to obtain the carbide in-situ reinforced high temperature and high strength wear-resistant material.
[0013] Preferably, the ball milling balls are made of zirconium dioxide, and the ball-to-material ratio is 5 to 15:1.
[0014] Preferably, the grinding aid for ball milling is methanol; the volume ratio of the total mass of the M2AlC phase and Ni to the grinding aid is 3 to 10:1.
[0015] Preferably, the rotation speed of the ball mill is 200 to 500 r / min, and the total ball milling time is 10 to 30 h.
[0016] Preferably, the vacuum degree of the sintering is 10 -3 ~10 -1 Pa, the sintering pressure is 20~30MPa.
[0017] Preferably, the heating rate of the sintering is 5-10° C. / min, the target temperature of the sintering is 1150-1250° C., and the holding time after reaching the target temperature is 30-120 min.
[0018] The present invention also provides the use of the carbide in-situ enhanced high-temperature and high-strength wear-resistant material in aircraft engine parts, high-performance cutting tool parts or drilling tool parts.
[0019] The beneficial effects of the present invention are:
[0020] The present invention provides a carbide in-situ reinforced high-temperature and high-strength wear-resistant material, which is prepared from the following raw materials in molar fraction: 10-30% of M2AlC phase (one or more of V2AlC, Nb2AlC and Ta2AlC), and the balance of Ni. During the preparation, the M2AlC phase and Ni are mixed, and ball milling and sintering are performed in sequence to obtain the carbide in-situ reinforced high-temperature and high-strength wear-resistant material. The present invention prepares the carbide in-situ reinforced high-temperature and high-strength wear-resistant material by compounding Ni and M2AlC phases and adopting a powder metallurgy method (ball milling + vacuum hot pressing sintering). During the hot pressing sintering process, Ni-based solid solution (γ phase), Ni3Al (γ′ phase), Ni3(Al, V), Ni3(Al, Nb), NiAl and other matrix phases and VC are generated in situ. x , NbC x Carbide strengthening phase. Since carbides are generated in situ, they overcome the shortcomings of poor wettability of added carbides with the metal matrix, easy detachment, high brittleness, and premature fracture of the material. At room temperature, the composite strengthening mechanism of solid solution strengthening, γ′ phase precipitation strengthening, intermetallic compound strengthening, and in-situ carbide strengthening ensures that the material has good mechanical properties; in-situ carbides improve the wear resistance of the material. At high temperatures, Ni-based solid solution, γ′ phase, V, Nb-doped γ′ phase, NiAl intermetallic compound, etc. still have high mechanical properties; and the in-situ generated VC x Although oxidized, vanadium oxide (V x O y ) and vanadates (Ni3V2O8, Ni2V2O7, AlVO3), while NbC x Carbides are very stable and can still exist stably during high temperature friction, and niobium oxide (Nb x O y ), niobates (AlNbO3, NiNb2O6) also have good wear resistance, making the material have excellent lubrication and wear resistance. In addition, the present invention does not add lubricants, but the NiO, vanadium oxide, niobium oxide, vanadate, niobate and other phases generated during the high-temperature friction reaction are high-temperature lubricants, which can play a lubricating and anti-wear role at high temperatures.
[0021] The material system of the present invention is simple, and there are only two raw materials: Ni and M2AlC (M is the third subgroup element V, Nb, Ta). During the hot pressing sintering process, Al atoms in M2AlC are easily released from the lattice and react with Ni to form Ni matrix solid solution, Ni3Al, NiAl and other phases (depending on the ratio of Ni to M2AlC phases). At the same time, M2AlC is in-situ converted into MC x Carbide. A simple system is used to generate a matrix phase and a reinforcement phase with both high strength and wear resistance. In addition, a high-temperature lubricant is generated in situ on the surface through a tribochemical reaction at high temperature. The internal structure of the material still maintains the Ni matrix solid solution, Ni3Al, NiAl and other organizational structures, achieving the optimization and unification of the mechanical properties and friction and wear properties of the material at high temperatures. The obtained product can be used for aircraft engine turbine blades and outer rings, blade crown meshing surfaces, high-performance cutting, drilling tools and other parts that require high mechanical properties and wear resistance at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The X-ray characterization image and SEM characterization image of the high-temperature and high-strength wear-resistant material reinforced with carbide in situ in Example 1; Figure 1 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide;
[0023] Figure 2 The X-ray characterization image and SEM characterization image of the high-temperature and high-strength wear-resistant material reinforced with carbide in situ in Example 2; Figure 2 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide;
[0024] Figure 3 The X-ray characterization image and SEM characterization image of the high-temperature and high-strength wear-resistant material reinforced with carbide in situ in Example 3; Figure 3 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide;
[0025] Figure 4 The X-ray characterization image and SEM characterization image of the high-temperature and high-strength wear-resistant material reinforced with carbide in situ in Example 4; Figure 4In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ by carbide;
[0026] Figure 5 The X-ray characterization image and SEM characterization image of the high-temperature and high-strength wear-resistant material reinforced with carbide in situ in Example 5; Figure 5 In the figure, (a) is an X-ray characterization image (Intensity) of the high temperature and high strength wear-resistant material reinforced with carbide in situ, and (b) is an SEM characterization image of the high temperature and high strength wear-resistant material reinforced with carbide in situ. DETAILED DESCRIPTION
[0027] The present invention provides a carbide in-situ reinforced high-temperature and high-strength wear-resistant material, which is prepared from raw materials containing the following molar fractions:
[0028] M2AlC phase 10-30%, Ni balance;
[0029] The M2AlC phase includes one or more of V2AlC, Nb2AlC and Ta2AlC.
[0030] In the present invention, the particle size of the M2AlC phase is preferably ≤20 μm, more preferably ≤18 μm, and more preferably ≤15 μm; the particle size of Ni is preferably ≤48 μm, more preferably ≤45 μm, and more preferably ≤40 μm.
[0031] In the present invention, the molar fraction of the M2AlC phase is 10 to 30%, preferably 15 to 25%, more preferably 17 to 23%, and even more preferably 20%.
[0032] The present invention also provides a method for preparing the carbide in-situ enhanced high-temperature and high-strength wear-resistant material, comprising the following steps:
[0033] The M2AlC phase and Ni are mixed, ball milled and sintered in sequence to obtain the carbide in-situ reinforced high temperature and high strength wear-resistant material.
[0034] In the present invention, the material of the ball milling balls is preferably zirconium dioxide, the material of the ball milling jar is preferably zirconium dioxide, and the ball-to-material ratio of the ball milling is preferably 5-15:1, more preferably 7-13:1, and more preferably 10-11:1.
[0035] In the present invention, ball milling is carried out under the protection of a grinding aid, and the grinding aid for ball milling is preferably methanol (anhydrous methanol); the volume ratio of the total mass of the M2AlC phase and Ni to the grinding aid is preferably 3-10:1, further preferably 4-7:1, and more preferably 5-6:1.
[0036] In the present invention, the rotation speed of the ball mill is preferably 200-500 r / min, more preferably 250-450 r / min, more preferably 300-400 r / min; the total ball milling time is preferably 10-30 h, more preferably 12-25 h, more preferably 20-22 h.
[0037] In the present invention, the ball milling is preferably carried out in a planetary ball mill or a high-energy ball mill. When ball milling is carried out in a planetary ball mill, a higher ball milling speed is used; when ball milling is carried out in a high-energy ball mill, a lower ball milling speed is used.
[0038] In the present invention, ball milling is preferably performed intermittently; preferably, ball milling is performed for 20 to 40 minutes, and then stopped for 20 to 40 minutes (further preferably, ball milling is performed for 25 to 35 minutes, and then stopped for 25 to 35 minutes; more preferably, ball milling is performed for 30 minutes, and then stopped for 30 minutes), and the ball milling-stopping process is repeated until the total ball milling time meets the above-defined range, thereby completing the ball milling.
[0039] In the present invention, after the ball milling is completed, the mixed powder obtained by the ball milling is placed in a graphite mold whose inner wall is coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering.
[0040] In the present invention, the vacuum degree of sintering is preferably 10 -3 ~10 -1 Pa, more preferably 8*10 -3 ~5*10 - 2 Pa, preferably 9*10 -3 ~10 -2 Pa; the sintering pressure is preferably 20 to 30 MPa, more preferably 22 to 28 MPa, and more preferably 25 to 26 MPa.
[0041] In the present invention, the sintering heating rate is preferably 5-10°C / min, more preferably 6-9°C / min, and more preferably 7-8°C / min; the sintering target temperature is preferably 1150-1250°C, more preferably 1170-1230°C, and more preferably 1200-1210°C; the holding time after reaching the target temperature is preferably 30-120min, more preferably 50-100min, and more preferably 60-90min.
[0042] In the present invention, after sintering, the material is cooled to room temperature along with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0043] The present invention also provides the use of the carbide in-situ enhanced high-temperature and high-strength wear-resistant material in aircraft engine parts, high-performance cutting tool parts or drilling tool parts.
[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] Example 1
[0046] This embodiment provides a carbide in-situ enhanced high-temperature and high-strength wear-resistant material, which is prepared from the following raw materials in molar fractions: M2AlC phase (V2AlC) 10%, particle size 20μm; Ni 90%, particle size 48μm;
[0047] The preparation method comprises the following steps: V2AlC and Ni are mixed and ball-milled, and the ball-milling conditions are set as follows: the ball milling ball is made of zirconium dioxide, the ball milling jar is made of zirconium dioxide, the ball-to-material ratio is 10:1, anhydrous methanol is added as a grinding aid, the volume ratio of the total mass of V2AlC and Ni to methanol is 5:1, the ball milling is carried out in a high-energy ball mill, the ball milling speed is 250r / min, and the total ball milling time is 20h (in the ball milling process, mill for 30min, stop for 30min, and repeat the milling-stop process); after the ball milling is completed, the mixed powder obtained by the ball milling is loaded into a graphite mold with an inner wall coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering, and the sintering conditions are set as follows: the vacuum degree of sintering is 10 -1 Pa, pressure is 25MPa, heating rate is 10℃ / min, target temperature is 1200℃, holding time is 60min. After sintering, it is cooled to room temperature with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0048] The carbide in-situ enhanced high temperature and high strength anti-wear material prepared in this embodiment was subjected to X-ray characterization and SEM characterization to obtain an X-ray characterization image and a SEM characterization image of the carbide in-situ enhanced high temperature and high strength anti-wear material in this embodiment, as shown in FIG. Figure 1 As shown; Figure 1 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides. Figure 1 It can be seen that the high-temperature, high-strength and wear-resistant material reinforced with carbides in situ contains four phases: Ni-based solid solution, in-situ generated γ′ (Ni3Al), V-doped γ′ phase Ni3 (Al, V) and in-situ generated carbides VC.
[0049] The carbide in-situ reinforced high temperature and high strength anti-wear material prepared in this embodiment was tested for performance at room temperature, 800°C and 1000°C, respectively, and the performance test results of the carbide in-situ reinforced high temperature and high strength anti-wear material in this embodiment were obtained, as shown in Table 1. The test method for tensile strength is as follows: the tensile strength of the material is tested using an electronic universal material testing machine, the sample to be tested is a plate-shaped sample, the gauge section size is 20mm (length) × 4mm (width) × 2mm (thickness), the test temperatures are room temperature, 800°C and 1000°C, respectively, and the tensile rate is 0.1mm / min; the test method for compressive strength is as follows: the compressive strength of the material is tested using an electronic universal testing machine, the sample size is The test temperatures were room temperature, 800°C and 1000°C, respectively, and the strain rate was 0.36 mm / min. The friction coefficient and wear rate test methods were as follows: The test was conducted on a UMT-3 high temperature friction tester. The disc was the carbide in-situ reinforced high temperature and high strength wear-resistant material prepared in this embodiment, and the size was The dual ball is The Al2O3 ceramic ball was tested with a load of 10N, a sliding rate of 200r / min, a rotation radius of 5mm, a running time of 60min, and a test temperature of room temperature and 800℃ (due to the limitation of the friction tester itself, the maximum test temperature can only reach 800℃). Although the tribological properties were only tested to 800℃, it can be inferred from the microstructure that NiO, Ni3V2O8, Ni2V2O7, etc. generated at high temperatures are excellent high-temperature lubricants, and the material also has good tribological properties at 1000℃.
[0050] Table 1 Performance test results of carbide in-situ enhanced high temperature and high strength wear-resistant materials in Example 1
[0051] temperature Room temperature 800℃ 1000℃ Tensile strength(MPa) 796.72±17.49 229.08±10.31 40.73±2.95 Compressive strength(MPa) 1991.83±56.22 362.48±15.36 68.18±4.41 Friction coefficient 0.70±0.05 0.30±0.01 —— <![CDATA[Wear rate (×10 -5 mm 3 / Nm)]]> 8.75±0.55 1.22±0.45 ——
[0052] In Table 1, — indicates not measured.
[0053] Example 2
[0054] This embodiment provides a carbide in-situ enhanced high temperature and high strength wear-resistant material, which is prepared from the following raw materials in molar fraction: M2AlC phase (V2AlC) 20%, particle size 15μm; Ni 80%, particle size 40μm;
[0055] The preparation method comprises the following steps: V2AlC and Ni are mixed and ball-milled, and the ball-milling conditions are set as follows: the ball milling ball is made of zirconium dioxide, the ball milling jar is made of zirconium dioxide, the ball-to-material ratio is 10:1, anhydrous methanol is added as a grinding aid, the volume ratio of the total mass of V2AlC and Ni to methanol is 5:1, the ball milling is carried out in a planetary ball mill, the ball milling speed is 400r / min, and the total ball milling time is 15h (during the ball milling process, mill for 30min, stop for 30min, and repeat the milling-stop process); after the ball milling is completed, the mixed powder obtained by the ball milling is loaded into a graphite mold with an inner wall coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering, and the sintering conditions are set as follows: the vacuum degree of sintering is 10 -2 Pa, pressure is 30MPa, heating rate is 10℃ / min, target temperature is 1150℃, holding time is 60min. After sintering, it is cooled to room temperature with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0056] The carbide in-situ enhanced high temperature and high strength anti-wear material prepared in this embodiment was subjected to X-ray characterization and SEM characterization to obtain an X-ray characterization image and a SEM characterization image of the carbide in-situ enhanced high temperature and high strength anti-wear material in this embodiment, as shown in FIG. Figure 2 As shown; Figure 2 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides. Figure 2 It can be seen that the high-temperature, high-strength, wear-resistant material reinforced with carbides in situ is composed of Ni-based solid solution, Ni3Al, Ni3(Al, V) and in-situ generated non-stoichiometric ratio VC x (VC 0.75 )composition.
[0057] The carbide in-situ reinforced high-temperature and high-strength wear-resistant material prepared in this embodiment was subjected to performance tests at room temperature, 800°C and 1000°C (the testing method is the same as in Example 1), and the performance test results of the carbide in-situ reinforced high-temperature and high-strength wear-resistant material in this embodiment were obtained, as shown in Table 2.
[0058] Table 2 Performance test results of carbide in-situ enhanced high temperature and high strength wear-resistant materials in Example 2
[0059] temperature Room temperature 800℃ 1000℃ Tensile strength(MPa) 449.33±22.44 379.34±10.71 77.96±3.75 Compressive strength(MPa) 2370.97±111.73 864.79±15.11 138.49±10.56 Friction coefficient 0.69±0.01 0.30±0.001 —— <![CDATA[Wear rate (×10 -5 mm 3 / Nm)]]> 4.94±0.43 0.47±0.33 ——
[0060] In Table 2, — indicates not measured.
[0061] It can be seen from Table 2 that the carbide in-situ reinforced high-temperature and high-strength wear-resistant material prepared in this embodiment has good mechanical properties and wear resistance at room temperature and high temperature. This is due to the composite strengthening effect of γ phase, γ′ phase, V-doped γ′ phase and in-situ carbide and the anti-wear effect of Ni3V2O8, NiO, etc. generated at high temperature.
[0062] Example 3
[0063] This embodiment provides a carbide in-situ enhanced high-temperature and high-strength wear-resistant material, which is prepared from the following raw materials in molar fractions: M2AlC phase (V2AlC) 30%, particle size 20μm; Ni 70%, particle size 45μm;
[0064] The preparation method comprises the following steps: V2AlC and Ni are mixed and ball-milled, and the ball-milling conditions are set as follows: the ball milling ball is made of zirconium dioxide, the ball milling jar is made of zirconium dioxide, the ball-to-material ratio is 10:1, anhydrous methanol is added as a grinding aid, the volume ratio of the total mass of V2AlC and Ni to methanol is 4:1, the ball milling is carried out in a high-energy ball mill, the ball milling speed is 250r / min, and the total ball milling time is 10h (in the ball milling process, the milling is performed for 30min, the stop is performed for 30min, and the milling-stop process is repeated); after the ball milling is completed, the mixed powder obtained by the ball milling is loaded into a graphite mold with an inner wall coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering, and the sintering conditions are set as follows: the vacuum degree of sintering is 10 -3 Pa, pressure is 30MPa, heating rate is 10℃ / min, target temperature is 1200℃, holding time is 30min. After sintering, it is cooled to room temperature with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0065] The carbide in-situ enhanced high temperature and high strength anti-wear material prepared in this embodiment was subjected to X-ray characterization and SEM characterization to obtain an X-ray characterization image and a SEM characterization image of the carbide in-situ enhanced high temperature and high strength anti-wear material in this embodiment, as shown in FIG. Figure 3 As shown; Figure 3 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides. Figure 3 It can be seen that the high temperature and high strength wear-resistant material reinforced by carbide in situ is composed of Ni3Al, NiAl, and in-situ generated non-stoichiometric carbide VC 0.845 and V2C.
[0066] The carbide in-situ reinforced high-temperature and high-strength wear-resistant material prepared in this embodiment was subjected to performance tests at room temperature, 800°C and 1000°C (the testing method is the same as in Example 1), and the performance test results of the carbide in-situ reinforced high-temperature and high-strength wear-resistant material in this embodiment were obtained, as shown in Table 3.
[0067] Table 3 Performance test results of carbide in-situ reinforced high temperature and high strength wear-resistant materials in Example 3
[0068] temperature Room temperature 800℃ 1000℃ Tensile strength(MPa) 342.91±16.90 429.33±5.28 66.32±4.35 Compressive strength(MPa) 2170.2±88.12 627.42±44.38 111.46±6.93 Friction coefficient 0.63±0.06 0.24±0.03 —— <![CDATA[Wear rate (×10 -5 mm 3 / Nm)]]> 1.99±0.86 2.06±0.74 ——
[0069] In Table 3, — indicates not measured.
[0070] Example 4
[0071] This embodiment provides a carbide in-situ enhanced high temperature and high strength wear-resistant material, which is prepared from the following raw materials in molar fraction: M2AlC phase (Nb2AlC) 10%, particle size 15μm; Ni 90%, particle size 48μm;
[0072] The preparation method comprises the following steps: mixing Nb2AlC and Ni for ball milling, setting the conditions of ball milling as follows: the ball milling ball is made of zirconium dioxide, the ball milling jar is made of zirconium dioxide, the ball-to-material ratio is 10:1, anhydrous methanol is added as a grinding aid, the volume ratio of the total mass of Nb2AlC and Ni to methanol is 6:1, ball milling is carried out in a high-energy ball mill, the ball milling speed is 250r / min, and the total ball milling time is 20h (in the ball milling process, milling for 30min, stopping for 30min, and repeating the milling-stopping process); after the ball milling is completed, the mixed powder obtained by ball milling is loaded into a graphite mold with an inner wall coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering, and the sintering conditions are set as follows: the vacuum degree of sintering is 10 -3 Pa, the pressure is 25MPa, the heating rate is 8℃ / min, the target temperature is 1200℃, the holding time is 120min. After the sintering is completed, it is cooled to room temperature with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0073] The carbide in-situ enhanced high temperature and high strength anti-wear material prepared in this embodiment was subjected to X-ray characterization and SEM characterization to obtain an X-ray characterization image and a SEM characterization image of the carbide in-situ enhanced high temperature and high strength anti-wear material in this embodiment, as shown in FIG. Figure 4 As shown; Figure 4 In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides. Figure 4It can be seen that the high-temperature and high-strength wear-resistant material reinforced by carbide in situ is composed of Ni-based solid solution, Ni3Nb, Ni3Al, in-situ generated NbC and a small amount of Al2O3.
[0074] The carbide in-situ reinforced high-temperature and high-strength wear-resistant material prepared in this embodiment was subjected to performance tests at room temperature, 800°C and 1000°C respectively (the testing method is the same as that in Example 1), and the performance test results of the carbide in-situ reinforced high-temperature and high-strength wear-resistant material in this embodiment were obtained, as shown in Table 4.
[0075] Table 4 Performance test results of carbide in-situ reinforced high temperature and high strength wear-resistant materials in Example 4
[0076]
[0077] In Table 4, — indicates not measured.
[0078] Example 5
[0079] This embodiment provides a carbide in-situ enhanced high temperature and high strength wear-resistant material, which is prepared from the following raw materials in molar fraction: M2AlC phase (Nb2AlC) 30%, particle size 15μm; Ni 70%, particle size 40μm;
[0080] The preparation method comprises the following steps: mixing Nb2AlC and Ni for ball milling, and setting the ball milling conditions as follows: the ball milling balls are made of zirconium dioxide, the ball milling jar is made of zirconium dioxide, the ball-to-material ratio is 10:1, anhydrous methanol is added as a grinding aid, the volume ratio of the total mass of Nb2AlC and Ni to methanol is 5:1, the ball milling is carried out in a planetary ball mill, the ball milling speed is 400r / min, and the total ball milling time is 15h (in the ball milling process, mill for 30min, stop for 30min, and repeat the milling-stop process); after the ball milling is completed, the mixed powder obtained by the ball milling is loaded into a graphite mold with an inner wall coated with hexagonal boron nitride, and then placed in a vacuum hot pressing sintering furnace for sintering, and the sintering conditions are set as follows: the vacuum degree of sintering is 10 -1 Pa, pressure is 30MPa, heating rate is 5℃ / min, target temperature is 1150℃, holding time is 90min. After sintering, it is cooled to room temperature with the furnace to obtain a high-temperature and high-strength wear-resistant material with carbide in-situ reinforcement.
[0081] The carbide in-situ enhanced high temperature and high strength anti-wear material prepared in this embodiment was subjected to X-ray characterization and SEM characterization to obtain an X-ray characterization image and a SEM characterization image of the carbide in-situ enhanced high temperature and high strength anti-wear material in this embodiment, as shown in FIG. Figure 5 As shown; Figure 5In the figure, (a) is an X-ray characterization image (Intensity) of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides, and (b) is an SEM characterization image of a high-temperature, high-strength, wear-resistant material reinforced in situ with carbides. Figure 5 It can be seen that the carbide in-situ reinforced high-temperature and high-strength wear-resistant material is composed of in-situ generated carbides (NbC, Nb4Ni2C), Ni3Nb, NiAl, Al3Nb, Al2O3, etc.
[0082] The carbide in-situ reinforced high-temperature and high-strength wear-resistant material prepared in this embodiment was subjected to performance tests at room temperature, 800°C and 1000°C respectively (the testing method is the same as that in Example 1), and the performance test results of the carbide in-situ reinforced high-temperature and high-strength wear-resistant material in this embodiment were obtained, as shown in Table 5.
[0083] Table 5 Performance test results of carbide in-situ reinforced high temperature and high strength wear-resistant materials in Example 5
[0084]
[0085] In Table 5, — indicates not measured.
[0086] It can be seen from Table 5 that although the mechanical properties of the carbide in-situ enhanced high-temperature and high-strength wear-resistant material prepared in this embodiment are slightly lower at room temperature, its tensile, compression and wear resistance at high temperature are all good. This is attributed to the fact that more in-situ carbides (NbC, Nb4Ni2C) are generated, and the carbides are very stable and still exist after friction at 800°C, which can enhance the wear resistance.
[0087] It can be seen from the above embodiments that the material system of the present invention is simple, and there are only two raw materials: Ni and M2AlC (M is the third subgroup element V, Nb, Ta). During the hot pressing sintering process, Al atoms in M2AlC are easily released from the lattice and react with Ni to form Ni matrix solid solution, Ni3Al, NiAl and other phases (depending on the ratio of Ni to M2AlC phases). At the same time, M2AlC is in-situ converted into MC x Carbide. A simple system is used to generate a matrix phase and a reinforcement phase with both high strength and wear resistance. In addition, a high-temperature lubricant is generated in situ on the surface through a tribochemical reaction at high temperature. The internal structure of the material still maintains the Ni matrix solid solution, Ni3Al, NiAl and other organizational structures, achieving the optimization and unification of the mechanical properties and friction and wear properties of the material at high temperatures. The obtained product can be used for aircraft engine turbine blades and outer rings, blade crown meshing surfaces, high-performance cutting, drilling tools and other parts that require high mechanical properties and wear resistance at high temperatures.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A carbide in-situ reinforced high temperature and high strength wear-resistant material, characterized in that: Prepared from raw materials containing the following mole fractions: M2AlC phase 10-30%, Ni balance; The M2AlC phase includes one or more of V2AlC, Nb2AlC and Ta2AlC.
2. The carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 1, characterized in that: The particle size of the M2AlC phase is ≤20 μm, and the particle size of Ni is ≤48 μm.
3. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 1 or 2, characterized in that: It includes the following steps: The M2AlC phase and Ni are mixed, ball milled and sintered in sequence to obtain the carbide in-situ reinforced high temperature and high strength wear-resistant material.
4. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 3, characterized in that: The material of the ball milling balls is zirconium dioxide, and the ball-to-material ratio of the ball milling is 5 to 15:
1.
5. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 4, characterized in that: The grinding aid of ball milling is methanol; the volume ratio of the total mass of M2AlC phase and Ni to the grinding aid is 3-10:
1.
6. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 5, characterized in that: The rotation speed of the ball mill is 200-500 r / min, and the total ball milling time is 10-30 hours.
7. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 6, characterized in that: The sintering vacuum degree is 10 -3 ~10 -1 Pa, the sintering pressure is 20~30MPa.
8. The method for preparing the carbide in-situ reinforced high temperature and high strength wear-resistant material according to claim 7, characterized in that: The heating rate of the sintering is 5-10°C / min, the target temperature of the sintering is 1150-1250°C, and the holding time after reaching the target temperature is 30-120min.
9. Use of the carbide in-situ reinforced high-temperature and high-strength wear-resistant material according to claim 1 or 2 in aircraft engine parts, high-performance cutting tool parts or drilling tool parts.
Citation Information
Patent Citations
NiCr-Al2O3 self-lubricating composite material and preparation method thereof
CN103572137A
Nickel-based high-temperature self-lubricating composite material and preparation method thereof
CN105441707A
Nickel base self-lubricating composite material with wide temperature range and preparation method of composite material
CN105986147A
Nickel alloy base high-temp. self-lubricating material
CN1073727A
Self lubricated Ni-Cr base alloy
CN1082620A